2020
DOI: 10.3390/nu12092762
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Pathogenesis of Non-Alcoholic Fatty Liver Disease: Gut-Derived Lipopolysaccharides and Oxidative Stress

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease worldwide. The intricate NAFLD pathogenesis is summarized by the multiple-hits hypothesis, which combines all the environmental and genetic factors that promote the development of NAFLD into a single scenario. Among these, bacterial lipopolysaccharides (LPS) are derived from the overgrowth of Gram-negative bacteria and translocated mainly as a consequence of enhanced intestinal permeability. Furthermore, oxidative stress is incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 100 publications
1
105
0
Order By: Relevance
“…Oxidative stress plays a key role in the pathogenesis of NAFLD and progression to NASH (reviewed recently in [79]). Nobili et al [80] found that oxidative stress is highly prevalent in pediatric NAFLD.…”
Section: Mitochondrial Dysfunction and Oxidative Stress In The Progression Of Pediatric Nafldmentioning
confidence: 99%
“…Oxidative stress plays a key role in the pathogenesis of NAFLD and progression to NASH (reviewed recently in [79]). Nobili et al [80] found that oxidative stress is highly prevalent in pediatric NAFLD.…”
Section: Mitochondrial Dysfunction and Oxidative Stress In The Progression Of Pediatric Nafldmentioning
confidence: 99%
“…On the one hand, the endotoxins entering the blood circulation not only directly damage the intestinal mucosal epithelial cells, but also induce intestinal microvasculature contractions and intestinal tissue ischemia and hypoxia, leading to excessive ROS production. Meanwhile, the increase in the intestinal permeability augments endotoxin absorption, which is also a huge burden on the liver (28,29). On the other hand, because of the presence of the intestine-liver axis, the endotoxins entering the blood circulation also act directly on the liver, causing its in ammation by activating Toll-like receptors (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the increase in the intestinal permeability augments endotoxin absorption, which is also a huge burden on the liver (28,29). On the other hand, because of the presence of the intestine-liver axis, the endotoxins entering the blood circulation also act directly on the liver, causing its in ammation by activating Toll-like receptors (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, in advanced PCOS with accompanying disease associated with metabolic syndrome and the steatosis of internal organs (especially non-alcoholic fatty liver disease), herbs and their extracts with proven properties should be considered for their hepatoprotective activities [ 136 ]. These substances include the silymarin contained in milk thistle ( Silybum marianum ) [ 137 , 138 ] and sesquiterpenes and antioxidant-active ingredients in artichoke ( Cynara Cardunculus ) extract [ 139 , 140 ].…”
Section: Lifestyle Changesmentioning
confidence: 99%